2003
DOI: 10.1007/s00360-003-0336-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH regulation in rainbow trout (Oncorhynchus mykiss) hepatocytes: the activity of sodium/proton exchange is oxygen-dependent

Abstract: We studied pH regulation in freshly isolated rainbow trout hepatocytes using microspectrofluorometry with the fluorescent dye BCECF. In accordance with earlier data on rainbow trout hepatocytes, ion substitution (N-methyl D-glucamine for sodium and gluconate for chloride) and transport inhibitor [10 microM M methyl isobutyl amiloride (MIA) to inhibit sodium/proton exchange and 100 microM DIDS to inhibit bicarbonate transport] studies in either Hepes-buffered or bicarbonate/carbon dioxide-buffered media (extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…This observation makes it tempting to suggest that this radical species is the second messenger involved in transferring information from so far unknown primary oxygen-binding protein(s) to ion transporters. Notably, treatment of hepatocytes with MPG suppresses proton extrusion mediated by Na + /H + exchanger (Tuominen et al, 2003). The latter finding suggests common regulatory pathways for oxygen-induced regulation of both ion transporters.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This observation makes it tempting to suggest that this radical species is the second messenger involved in transferring information from so far unknown primary oxygen-binding protein(s) to ion transporters. Notably, treatment of hepatocytes with MPG suppresses proton extrusion mediated by Na + /H + exchanger (Tuominen et al, 2003). The latter finding suggests common regulatory pathways for oxygen-induced regulation of both ion transporters.…”
Section: Discussionmentioning
confidence: 79%
“…Data we have obtained previously on oxygen sensitivity of Na + /H + exchanger reveal that this transporter is activated by hypoxic treatment (Tuominen et al, 2003). If this were the case, hypoxic conditions should result in gradual Na + accumulation as passive Na + uptake is increased and active efflux downregulated.…”
Section: Discussionmentioning
confidence: 90%
“…To further substantiate our conclusion on the dependence of Na ϩ /H ϩ exchange activity on an intact actin-based cytoskeleton, we also investigated the impact of CB on pH i recovery following an acid load, which, as shown in previous studies on trout hepatocytes (23,60,63), is to a major extent dependent on Na ϩ /H ϩ exchange and, to a minor extent, on a SITSsensitive anion transporter. We observed that upon acidification after an NH 4 ϩ prepulse in the presence of SITS, control cells clearly recovered pH i , whereas in CB-treated cells, no such recovery was noted.…”
Section: Discussionmentioning
confidence: 84%
“…The Prompted by our findings on proton secretion rates, we suspected that these different pH i response patterns could have been caused by an effect of cytoskeletal disruption on the Na ϩ /H ϩ exchanger. To investigate this possibility, we examined the pH i recovery in controls and CB-treated hepatocytes after the induction of an acid load, a condition known to strongly activate this ion transporter in trout hepatocytes (23,60,63). Intracellular acidification was achieved using the NH 4 ϩ prepulse technique (8,47) with concurrent addition of the inhibitor of Na ϩ -dependent Cl Ϫ /HCO 3 Ϫ exchange, SITS, to prevent compensatory activation of this transporter should Na ϩ /H ϩ exchange indeed have been diminished by the CB treatment.…”
Section: Effect Of Cytoskeleton Disrupting Agents On F-actin and Tubumentioning
confidence: 99%
“…rainbow trout hepatocytes have both NHE and Na ϩ /HCO 3 Ϫ cotransporters that contribute to pHi regulation during acid loading (18). In addition, NHE activity is higher at low O 2 levels, suggesting a role in correcting for anoxia-induced acidosis (54). On the other hand, in hepatocytes isolated from goldfish (Carassius auratus), a far more anoxia-tolerant fish, a sodium-independent Cl Ϫ /HCO 3 Ϫ exchanger was experimentally determined to increase acid excretion during chemical anoxia, implying that this pH regulatory mechanism may be contributing to hypoxia tolerance (29).…”
Section: Discussionmentioning
confidence: 99%